L'UTILISATION DU SUPPORT AUDIOVISUEL DANS L'APPRENTISSAGE DE LA PRODUCTION ÉCRITE D'UN TEXTE DESCRIPTIF - Mawarni, Nurani Dewi (2016)
This article aims to assess the use of media audiovisual to improve the skills descrptive writing of French language for senior high school students, and to find out the information abaout the advantages and disadvantages the used of this media. Through the application of this media, students are expected to be more motivated to practice and to be an active in writing French. The results showed that media audiovisual can be implemented in learning the French language for beginner, and make the learning process more interesting. Keywords: media audiovisual video, writing skill Artikel ini bertujuan untuk mengkaji penggunaan media audiovisuel untuk meningkatkan keterampilan menulis deskriptif bahasa Prancis pada siswa SMA (A1), dan untuk mengetahui kelebihan dan kekurangan dari penggunaan media ini dalam pembelajaran. Melalui penerapan media audiovisuel ini, diharapkan siswa dapat lebih termotivasi untuk berlatih dan menjadi aktif dalam menulis bahasa Prancis. Hasil kajian menunjukan bahwa media audiovisuel dapat diimplementasikan dalam pembelajaran bahasa Prancis bagi tingkat pemula, dan membuat proses belajar mengajar lebih menarik. Kata kunci: media audiovisual video, keterampilan menulis